Women Workers, Industrialization, Global Supply Chains and Corporate Codes of Conduct - Prieto-Carrón, Marina (Journal of business ethics, 2008)
The restructured globalized economy has provided women with employment opportunities. Globalisation has also meant a shift towards self-regulation of multinationals as part of the restructuring of the world economy that increases among others things, flexible employment practices, worsening of labour conditions and lower wages for many women workers around the world. In this context, as part of the global trend emphasising Corporate Social Responsibility (CSR) in the 1980s, one important development has been the growth of voluntary Corporate Codes of Conduct to improve labour conditions. This article reviews from a feminist interdisciplinary perspective the broad academic literature on women workers, covering the more classical debate on women workers in the industrialization process and entering into women workers in the global supply chains and women workers and corporate codes of conduct. The main argument is that this research on women workers is crucial to frame the issues of business ethics and in particular CSR and Codes of Conduct in the context of women in the global political economy. When this crucial knowledge is ignored, then the ethical policies of the companies also ignore the real situation of the women workers at the bottom of their supply chains.